2022
DOI: 10.3390/diagnostics12122927
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Low-Grade Glioma Surgery with Sodium Fluorescein: Efficient Localization for Removal and Association with Intraoperative Pathological Sampling

Abstract: Low-grade gliomas are among the most common CNS lesions in pediatrics and surgery is often the first-line treatment. Intraoperative tools have been developed to maximize the results of surgery, and in particular dyes such as sodium fluorescein (SF) have been investigated in high-grade adult lesions. The use of SF in pediatric low-grade gliomas is still unclear. We retrospectively reviewed 22 pediatric CNS low-grade gliomas operated on with SF from September 2021 to October 2022. A total of 86% of lesions showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Regardless of tumor type, sodium fluorescein demonstrated no significant difference in rate of fluorescence. Out of all studies included in our analysis, all demonstrated fluorescence rates above 77%, and 11 out of 15 demonstrated fluorescence rates > 90% [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Previous prospective cohort studies by Acerbi have shown a high specificity and sensitivity of fluorescein in glioma detection, citing numbers as high as 79.1% and 80.8%, respectively [12].…”
Section: Discussionmentioning
confidence: 89%
“…Regardless of tumor type, sodium fluorescein demonstrated no significant difference in rate of fluorescence. Out of all studies included in our analysis, all demonstrated fluorescence rates above 77%, and 11 out of 15 demonstrated fluorescence rates > 90% [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Previous prospective cohort studies by Acerbi have shown a high specificity and sensitivity of fluorescein in glioma detection, citing numbers as high as 79.1% and 80.8%, respectively [12].…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, helpful intraoperative fluorescence was identified by surgeons in most tumors of neuroepithelial tissue (HGGs, ependymoma, and glioneuronal tumor), metastases, and primary CNS lymphomas, but not in LGGs, meningiomas, and hemangioblastomas, reported by the FLUOCERTUM study (Falco et al 2019 ). In addition, research on pediatric LGGs-FGS demonstrated that 86% of the lesions showed fluorescence uptake, with 74% of them being helpful for resection (de Laurentis et al 2022 ). In line with the previous results, satisfactory fluorescence of tumor tissues under 560 nm filter was visualized in all 32 cases of HGGs undergoing fluorescence-guided resection included in the present study.…”
Section: Discussionmentioning
confidence: 99%